Pengaruh Penggunaan Catalytic Converter Kuningan Terhadap Emisi Gas Buang Mobil Antasari Evo I - Muhammad Nizar Ramadhan; Muhammad Adha; I. B. Nyoman Bayu Sivanatha; Muhammad Irza Irawan (Jurnal Teknik Mesin, 2023)
Vehicles are a means of transportation used by humans to support their daily activities. Its growth rate is getting higher, making this situation one of the causes of air pollution. One of the options in reducing dangerous motor exhaust emissions is to use a catalytic converter. Catalytic converter is a device that is installed in the exhaust channel of vehicles. The purpose of this study was to determine the effect of using a catalytic converter with a 2 mm thick brass plate material on the exhaust emissions of CO2, CO and HC in the Antasari Evo I. The test was carried out by comparing the exhaust emissions produced by the standard exhaust and the exhaust that was installed with a catalytic converter based on variations in engine idle speed, 2000 rpm, 2500 rpm and 3000 rpm. From the results of the study it was found that the effect of using a catalytic converter with brass plate material placed on the exhaust gas channel can reduce the maximum CO2 emission level by 42,85%, reduce the maximum CO2 emission level by 83%, and reduce the maximum HC emission level by 18,4 %.